2022
DOI: 10.3390/genes13020330
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Variants in the ATIC and ARID5B Genes on Therapeutic Failure with Imatinib in Patients with Chronic Myeloid Leukemia

Abstract: Chronic myeloid leukemia (CML) is a myeloproliferative neoplasm derived from the balanced reciprocal translocation of chromosomes 9 and 22 t (9q34 and 22q11), which leads to the formation of the Philadelphia chromosome and fusion of the BCR-ABL genes. The first-line treatment for CML is imatinib, a tyrosine kinase inhibitor that acts on the BCR-ABL protein. However, even though it is a target-specific drug, about 25% of patients do not respond to this treatment. The resistance mechanisms involved in this proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Shin and Park et al found that the polymorphism of ATIC (347 C > G, rs2372536) might affect the response of patients with osteosarcoma to methotrexate 32 . Karla et al showed that genetic variants of the ATIC gene affected the therapeutic efficacy of imatinib in chronic myeloid leukemia 33 . We used cBioPortal to analyze seven bladder cancer databases and two UTUC databases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Shin and Park et al found that the polymorphism of ATIC (347 C > G, rs2372536) might affect the response of patients with osteosarcoma to methotrexate 32 . Karla et al showed that genetic variants of the ATIC gene affected the therapeutic efficacy of imatinib in chronic myeloid leukemia 33 . We used cBioPortal to analyze seven bladder cancer databases and two UTUC databases.…”
Section: Discussionmentioning
confidence: 99%
“…32 Karla et al showed that genetic variants of the ATIC gene affected the therapeutic efficacy of imatinib in chronic myeloid leukemia. 33 We used cBioPortal to analyze seven bladder cancer databases and two UTUC databases. We found that FN1 had a higher proportion of mutations (4%) than the other six genes, and FN1 in UTUC had three mutation sites (2225 C > T, 889 C > T, and 1852G > A) (Supporting Information: Figure S3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studying children in the Amazon region of Brazil, authors investigated possible associations between NUDT15 (rs1272632214) and SLC22A1 (rs202220802) gene polymorphisms and response to treatment (BFM 2009 protocol) in acute lymphoid leukemia patients. Another myeloproliferative neoplasm, chronic myeloid leukemia (CML), and its first-line treatment imatinib are investigated by Cereja Pantoja et al, who conducted a large genotype association study on 32 polymorphisms in several carcinogenic genes, revealing interesting results [ 5 ]. To date, many oncological treatments recognize pharmacogenomic therapeutical suggestions.…”
mentioning
confidence: 99%
“…Three reviews focused on pharmacogenomics in oncology, psoriasis, and monogenic diabetes [ 6 , 7 , 8 ]. Furthermore, three research studies elucidate molecular aspects [ 9 ], genetic associations in large populations [ 5 ], and in selected ancestries [ 4 ].…”
mentioning
confidence: 99%